Endothelial control of vasodilation: integration of myoendothelial microdomain signalling and modulation by epoxyeicosatrienoic acids - Ellinsworth, David C. (Pflugers Arch, 2013)
Endothelium-derived epoxyeicosatrienoic acids (EETs) are fatty acid epoxides that play an important role in the control of vascular tone in selected coronary, renal, carotid, cerebral and skeletal muscle arteries. Vasodilation due to endothelium-dependent smooth muscle hyperpolarization (EDH) has been suggested to involve EETs as a transferable endothelium-derived hyperpolarizing factor. However, this activity may also be due to EETs interacting with the components of other primary EDH-mediated vasodilator mechanisms. Indeed, the transfer of hyperpolarization initiated in the endothelium to the adjacent smooth muscle via gap junction connexins occurs separately or synergistically with the release of K(+) ions at discrete myoendothelial microdomain signalling sites. The net effects of such activity are smooth muscle hyperpolarization, closure of voltage-dependent Ca(2+) channels, phospholipase C deactivation and vasodilation. The spatially localized and key components of the microdomain signalling complex are the inositol 1,4,5-trisphosphate receptor-mediated endoplasmic reticulum Ca(2+) store, Ca(2+)-activated K(+) (K(Ca)), transient receptor potential (TRP) and inward-rectifying K(+) channels, gap junctions and the smooth muscle Na(+)/K(+)-ATPase. Of these, TRP channels and connexins are key endothelial effector targets modulated by EETs. In an integrated manner, endogenous EETs enhance extracellular Ca(2+) influx (thereby amplifying and prolonging K(Ca)-mediated endothelial hyperpolarization) and also facilitate the conduction of this hyperpolarization to spatially remote vessel regions. The contribution of EETs and the receptor and channel subtypes involved in EDH-related microdomain signalling, as a candidate for a universal EDH-mediated vasodilator mechanism, vary with vascular bed, species, development and disease and thus represent potentially selective targets for modulating specific artery function.